Multicriteria analysis for flood mapping of Sungai Pahang - Ibrahim, Illyani; Asmawi, M. Zainora (2018)
The occurrence of floods is a natural disaster incidence that depends on the geographical, physical and rainfall. This study aims to investigate the geospatial analysis of flood in Sungai Pahang, Pahang. The objectives of the study are i) to analyse the use of factors for multi criteria analysis, and ii) to prepare a flood hazard mapping in Sungai Pahang, Pahang. Method used for this study is a multi-criteria analysis using Geographical Information System. Four important factors were used in this research; distance from the river, gradient, land cover and height of the land form. The finding show that the highly dense areas (such as Pekan and Kuantan) located close to the river are located inside the highest susceptible areas, which can give a high loss to the inhabitants in those particular areas. Thus, the recommendation suggests that determination of flood-prone areas of flood level 1 (protected area), level 2 (moderate sensitive rank), level 3 (controlled development area) and level 4 (development area) can be implement by the local authority in practice of development planning work.